The Effect of Lifestyle Modification Intervention with Motivational Construct on Dietary Macronutrient Intake among Obese Adults - SZ, Shahadan; A, Daud; ML, Md. Isa; M, Ibrahim; S, Deraman (IIUM Medical Journal Malaysia, 2019)
Introduction: An unhealthy dietary practice as a result of environmental and societal changes is increasingly exposed to adults. These unhealthy practices lead to an increased cardiometabolic risk, and obese adults are at a higher risk as compared to normal-weight adults. The best strategy to promote healthy lifestyle practices among Malaysian obese adult is still fragmented. Materials and Methods: A single-centre randomised controlled trial was carried out to determine the effect of the lifestyle modification intervention (LMI) with the motivational construct, in comparison to the current standard LMI on the dietary macronutrient intake among obese adults. The dietary macronutrient intake and changes in body weight were assessed at baseline and after six months. Seventy-nine participants completed the study. Results: Our finding showed that six months of LMI with motivational construct resulted in a higher reduction of total fat and cholesterol from the dietary intake as compared to the control. In addition, the participants in the intervention group had a significant body weight loss after six months (-1.97 kg, 95% CI: -0.324, 1.360, t(39) = 3.397, p = 0.002). Conclusion: This study demonstrates that the intervention had a meaningful impact on improving the dietary macronutrient intake, which is beneficial to support body weight loss in obese adults. Future trials with additional nutritional biomarkers are needed to extend these findings.